(untitled) (Fiep Bulletin - online, 2012)
In recent decades is the third age that population group, but grows, constituting one of the greatest achievements of this century. The quality of life reflects the way the individual is adapted to the activities of their daily lives, including their State of health that involves mental and physical well-being, functional and social inclusion. Related quality of life with the feeling of well-being, autonomy, independence and personal satisfaction, which are individual and vary from one individual to another, because of its subjectivity. Goal: draw the quality of life of elderly persons met in basic health Units. Methods: interviews were held with questions related to the profile of the quality of life, health care and access to the instrument (WHOQOL-Bref). Results: 259 participated in the survey (32%) of the 85 elderly males and 174 (68%) of females between the age of 60 to 100 years. In relation to the quality of life of older people have obtained the averages regarding domains: physical (3.3), psychological (3.8), social relations (3.6), environment (3.2), quality of life Global (3.7) and general perception of health (3.4), whereas a good quality of life. Conclusion: With this becomes apparent through this study that the fields displayed are parts of life of older people, however, so that the elderly maintain health, makes necessary to stimulate their participation in physical activities and laser, including socially-from changes in your lifestyle. It is the current generation perform a short-term planning, medium and long term, using the establishment of a policy of social welfare and health care of the elderly in Brazil, ensuring the legal rights and promoting the quality of life in the "best age".